ANALISIS KINERJA KEUANGAN DENGAN PENDEKATAN RASIO (Studi Pada PT. Bank Rakyat Indonesia (PERSERO)Tbk.) - Eka Bekti Oktaviani; Febriyanto - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2019)
Banks are a very important role for the Indonesian economy. The bank also runs because of thetrust of the community, if there is no trust from the community the bank may not run smoothly. This trustis channeled to the community in the form of credit to improve people's lives. Of the many banks thathave developed in Indonesia, customers must first evaluate the bank's performance to find out whetherthe bank is already good or not to be used as a storage place.The data used is quantitative data. The research method used is quantitative methods, namelyresearch methods that are based on the positivity philosophy used to examine the population or certainsample, this research focuses on aspects of the data originating from internal and external companies inthe process of collection and analysisBank management is advised to maintain and improve its performance so that it gets a verygood predicate. That way it will always be the choice of investors and customers in investing their funds.Banks must be careful in distributing loans that will allow risks for bad credit, which will cause adisruption to the liquidity ratio which will affect the customer's trust in the bank.